Nd:YAG Laser Posterior Capsulotomy and Visual Outcome - Bari, Khaleda Nazneen (Delta Medical College Journal, 2013)
Background: Neodymium-doped yttrium aluminum garnet (Nd:YAG) laser capsulotomy is a relatively noninvasive procedure that is used in the treatment of posterior capsular opacification (PCO). PCO is caused by proliferation of lens epithelial cells which causes fibrotic changes and wrinkling of the posterior capsule and results in decreased vision, glare, and other symptoms similar to that of the original cataract. Objective: To find out the visual outcome after performing Nd:YAG laser capsulotomy for PCO. Materials and method: A prospective clinical trial was carried out in National Institute of Ophthalmology (NIO), Dhaka, Bangladesh from January 2010 to June 2011 on purposively selected 70 adult subjects of both sexes who developed PCO within 2 months to more than 2 years after extracapsular cataract extraction with posterior chamber intra ocular lens implant. After thorough pre laser assessment Nd:YAG laser capsulotomy was carried out with Zeis VISULAS YAG II through Zeiss slit lamp under topical anesthesia. Data were recorded and expressed as proportion. Results: Out of the 70 subjects 40 were male and 30 were female. The average time interval of cataract surgery and Nd: YAG laser capsulotomy was 23 months. Capsular fibrosis (57.04%) was the predominant type of PCO. The pre laser visual acuity (VA) of more than 61.06% of eyes was 6/36 or below while 41.12% had VA hand movements to finger count. After Nd:YAG laser capsulotomy VA of 6/18 or better was achieved in 63.9% of eyes while 9.94% recovered to 6/9 and 11.36% achieved 6/6. None of these eyes showed further deterioration in VA. Conclusion: Nd:YAG laser capsulotomy for PCO is safe, effective and a rewarding procedure for improvement of vision. DOI: http://dx.doi.org/10.3329/dmcj.v1i1.14971 Delta Med Col J. Jan 2013;1(1):16-19